FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA DOSEN AKUNTANSI PADA PERGURUAN TINGGI DI PROPINSI BALI - Damayanthi, I Gusti Ayu Eka; Merkusiwati, Ni Ketut Lely (E-Jurnal Akuntansi, 2016)
This study wanted to identify and empirically examine the factors that affect the performance professor of accounting at state and private universities in the province of Bali. This research is important to improve the performance of state and private universities lecturers, increasing the competence of graduates and graduates improve stakeholder satisfaction. Based on the background, the purpose of the study was to determine whether the motivation affect performance Accounting lecturer, does affect the performance of Organizational Commitment Accounting lecturer and whether Commitment Accounting Profession affect the performance of lecturers. Research carried out in universities in the province of Bali. The research sample 61 respondents. The research data with the primary data of multiple linear regression analysis. Based on the results of testing the research model factors that affect the performance of the accounting faculty in the province of Bali with a sample of 61 lecturers showed motivation, organizational commitment and the commitment of the profession affect the performance of lecturers. Provide motivation to a very important job to improve performance. Motivation can be given in the form of an award in the form of reward for faculty who have a good performance and panisme for lecturers who violate the rules.
Keywords: motivation, organizational commitment, professional commitment, performance